Influence of auto-cross-linked hyaluronic acid gel on pregnancy rate and hysteroscopic outcomes following surgical removal of intra-uterine adhesions. (October 2015) - Thubert, T.; Dussaux, C.; Demoulin, G.; Rivain, A.-L.; Trichot, C.; Deffieux, X.
Abstract: Objective: To determine the effect of the use of auto-cross-linked hyaluronic acid (ACP) gel following hysteroscopic surgery on the prevention of intra-uterine adhesions (IUAs) and the pregnancy rate. Study design: An observational retrospective study of 90 patients who underwent hysteroscopic removal of IUAs was conducted between 2008 and 2013 at a tertiary university care centre. Thirty-two patients received ACP gel during hysteroscopic removal of IUAs, and the remaining 58 patients did not receive ACP gel. Controls were matched to cases according to infertility and severity of IUAs using the American Society for Reproductive Medicine (ASRM) score. Four to six weeks after surgery, patients underwent diagnostic hysteroscopy to determine the re-occurrence of IUAs or the presence of adhesions. The patients were contacted by telephone to answer a questionnaire concerning their fertility. The main outcomes were pregnancy rate and postoperative IUAs. Results: Pregnancy (viable or not) rates were not influenced by the use of ACP gel. The viable pregnancy rate was eight of 24 (33.3%) in the ACP gel group and 12 of 49 (24.5%) in the control group ( p = 0.427). The mean interval between surgery and pregnancy was 11.8 [standard deviation (SD) 10.5] months in the ACP group compared with 13.4 (SD 14.1) months in the control group ( p = 0.744). The mean ASRM score after surgery (hysteroscopic diagnosis at 4–6 weeks postoperatively) was equivalent in the two groups: 2.7 (SD 3.0) in the ACP gel group vs 2.6 (SD 3.2) in the control group ( p = 0.854). The mean follow-up was 45.2 months (interquartile range 33.2–52.7), with a loss to follow-up of 25% in the ACP gel group compared with 15.5% in the control group ( p = 0.817). Conclusion: Application of ACP gel did not prevent recurrence of IUAs and was not associated with an increased pregnancy rate. ACP gel should be used with caution pending assessment in a randomized control trial in a larger population.